Developing ESP Blended Learning for Academic Purposes of Course Materials for Students of English Education Study Program at Languages and Arts Faculty, Universitas Negeri Medan - Nora Ronita Dewi; Masitowarni Siregar; Anggraini Thesisia Saragih (Randwick International of Education and Linguistics Science Journal, 2020)
Industrial Revolution 4.0 has influenced many sectors, which are now a lot changes entering to human life by the presence of information technology.The use of power and data in the massive digital technology has become unlimited caused by its development at this present time. This study is aimed at developing the appropriate blended course materials of English for Specific Purposes for students of English Education Study Program, Languages and Arts Faculty, Universitas Negeri Medan. This study is focused on ESP Blended Learning Course Materials for Students of Seventh Semester of English Education Study Program. Research and Development (R & D) design is applied through six stages, there are 1). collecting information and data, 2). data analysis, 3). new materials design based on the needs analysis, 4). experts validation, 5). new material revision, and 6). final product. The instruments of collecting data are by applying two strategies: interview and questionnaires. The results show that the materials used in the 7th semester of English Education Study Program is developed through the implementation of the R&D simplification. The response of questionnaires signified low standard for the students after being analyzed. This results of the study developed ESP Blended Learning Course materials which focused on the following materials: Models and Teaching Strategies in ESP; Language Features: Linguistics and Grammar; Language Skills (Listening, Reading, Speaking, and Writing); Genre Text in ESP (Descriptive Text, Procedure Text, Analytical Exposition Text, and Argumentative Text).